Diagnosis of Rural Development Processes Based on the Stock of Social Capital and Social Networks: Approach from E-I Index - J. Javier Serrano; Javier Esparcia (Land, 2023)
Europe’s rural areas have suffered a continuous loss of human and economic capital from the beginning of the 20th century to the present day. In an attempt to alleviate the effects of this dynamic, the European Union has implemented the LEADER rural development programme since the 1990s (Liaisons Entre Actions de Développement de L’Economie Rurale). Among the many objectives of this policy, the social articulation of its populations stood out as a way of strengthening development processes. This article aims to provide a methodological approach to analyse and quantify the stock of social capital (SC) present in the social networks of rural areas after more than thirty years of European rural policy. Based on 160 interviews with stakeholders linked to rural development processes in rural areas of Spain and England from institutional, economic, social and technical sectors. The methodological approach of Social Network Analysis (SNA) has been used, and within this, the study of SNA indicators and the analysis of the E-I index have been integrated in order to analyse the stock of internal (bonding) and external (bridging) SC. The conclusions of this study clarify the role of stakeholders and their contribution to the stock of SC. The studied rural areas present a balance in internal and external relations, which shows a high stock of SC and an encouraging scenario for the development processes and, thus, for the success of the LEADER programme. Nevertheless, the participation of the actors in the LEADER programme in Spain still shows a worrying project class.